History of creation of association of domestic researchers of nature and doctors - Pichkur, T. V. (History of science and technology, 2014)
History of creation of association of domestic naturalists and doctors is illuminated in the article. It is shown that creation of this organization is small the special influence on development of world science, as stimulated creation of new laboratories for realization of experiments and formed new disciplines in natural science.